(3eQJbi GdhUhd Edi GdVQhQi ef GdCUhds - (3CHh HcQ eMeO Hf eMeO Hf YGUe GdCfOdSj GdZQfGWj,J (B829 (3g` s ((3CHjg Hf eMeO CYeQ s)
(3ChdgG (B:s
(3GdMeO ddg GdeMjW Ydeg GdSGHb GdNdb LejYkG MceI HYO , aGdYde CLd eYJfi Hg , hcd GdNjQ efg jLJfi , hGdfXe eOf efg cd eG bUi s
(3BNQgG (B:s
(3hGdCeQ gd eMdI GdhLhH hGdfgi gd JMQjeg GdeWdhH hGdMeO ddg GdPi HMeOg jSYO ef bOeg dbUOg Je s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV YHGQGJgG HGdMeQIs
(3fSNI eUMMIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B274s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B465s
Keywords: (3CUhd Gdabgs